Balai Pustaka and the Politics of Knowledge - Lisa Kuitert (Universitas Gadjah Mada, 2021)
During the colonial period of Indonesia the Dutch government was an important source of knowledge which was disseminated through the production of books, such as textbooks and other printed material. In response to the establishment of many new commercial printers and publishers, the colonial government, in 1917, set up its own publishing company, Balai Pustaka, which also published attractive and popular books. This new publishing house intentionally and unintentionally served several goals at a time that was characterized by the rise of young Indonesian intellectuals who were part of new political movements formed in the first decades of the 20th century.